Examining the influencing factors of turnover intention: Mediating and moderating effect of organizational commitment and Islamic work ethics - Rehman, Zia Ur (2022)
Drawing upon the social exchange theory and organizational justice theory, this study examined the influence of human resource practices (salary, training and development, performance appraisal and promotion opportunity), workplace incivility and authentic leadership style on employee‘s turnover intention. Moreover, this study also investigated the mediating effect of organizational commitment on these relationships, as well as the moderating role of Islamic work ethics on the relationship between organizational commitment and turnover intention. A total of 386 permanent charge nurses of five DHQ hospitals of Punjab, Pakistan participated in the study. The results demonstrated the significant direct relationships between salary, performance appraisal, promotion opportunity, workplace incivility, authentic leadership style, organizational commitment and turnover intention. Nonetheless, no significant direct relationship existed between training and development and turnover intention. Similarly, the study also found significant relationships between salary, performance appraisal, promotion opportunity, workplace incivility, authentic leadership style and organizational commitment except training and development. Furthermore, the bootstrapping results indicated that organizational commitment mediated the relationships between performance appraisal, promotion opportunity, workplace incivility, authentic leadership style and turnover intention. In contrast, this study did not find any mediation of organizational commitment between salary, training and development and turnover intention relationship. In addition, the results also revealed the significant role of Islamic work ethics in moderating the relationship between organizational commitment and turnover intention. In general, the findings showcased that turnover intention can be reduced through the examined key constructs of the study. Accordingly, the study has forwarded noteworthy claims regarding the mediating effect of organizational commitment on these variables and moderating effect of Islamic work ethics between organizational commitment and turnover intention. The study offers theoretical and practical contributions. This study also highlights the crucial role of these significant factors in reducing turnover intention amongst employees in the public healthcare sector. Lastly, limitations and future research directions are also provided.